Skin test and tick immune status in susceptible and resistant cattle in Brazil - Bechara, G. H. [UNESP]; Morelli Júnior., J. [UNESP]; Szabó, M. P. J. [UNESP] (Wiley, 2000)
A cutaneous hypersensitivity test (CHT) was used to correlate host resistance to ticks and type of reaction elicited to unfed larval extract-ULE of the cattle tick Boophilus microplus in European and Indian cattle. Twenty calves were separated into four groups of five animals each: naïve or preinfested Indian or European cattle. CHT was induced by intradermal inoculation of 0.1 ml of ULE cattle tick B. microplus (50 μg protein) in the calf ear. Ear thickness was measured using calipers before and 10 min, 1, 2, 6, 18, 24, 48, 72, 96, and 144 h postinoculation (PI). Preinfested European calves showed only an immediate type reaction with maximum response (75% increase in ear thickness) at 10 min PI. On the other hand, preinfested Indian calves presented an immediate response with maximum reaction (70% increase in ear thickness) between 10 min and one hour PI, and a delayed type reaction at 72 h PI (60% increase in ear thickness). These results point out the crucial role of the cellular immune response of cattle in the expression of resistance to cattle tick B. microplus. Skin test might be useful in the ranking of cattle according to the susceptibility/resistance to ticks.
Keywords: allergy test; animal experiment; animal model; Boophilus microplus; Brazil; cattle; cattle disease; conference paper; infection resistance; infection sensitivity; infestation; nonhuman; skin test; Animals; Cattle; Cattle Diseases; Disease Susceptibility; Europe; Immunity, Natural; India; Ixodes; Skin Tests; Tick Infestations; Acari; Animalia; Bos taurus